The World Upside Down = Le Monde à l'envers. - Hill, Richard; Walter Phillips Gallery, Banff (Banff : Walter Phillips Gallery - The Banff Centre for the Arts Banff, 2008)
Logan, Jim ; Stewart, Susan ; Durham, Jimmie ; Shonibare, Yinka ; General Idea ; Houle, Terrance ; Brown, Jarusha ; Cannon, T.C. ; Shimomura, Roger ; Niro, Shelley ; Blondeau, Lori ; Cox, Renée ; L'Hirondelle, Cheryl ; Daws, Jack ; Favell, Rosalie
Engels
Frans
Catalogue of the exhibition "The World Upside Down = Le monde à l'envers" at the Walter Phillips Gallery in Banff, 30.09.2006 - 07.03.2007
boek